2009
DOI: 10.1177/1091581809337736
|View full text |Cite
|
Sign up to set email alerts
|

Peri- and Postnatal Developmental Toxicity of Salcaprozate Sodium (SNAC) in Sprague-Dawley Rats

Abstract: Salcaprozate sodium (SNAC) (sodium 8-((2-hydroxybenzoyl) amino) octanoate, CAS RN 203787-91-1) is classified as an oral absorption promoter and may be a useful means for improving the absorption of certain nutrients and pharmaceutical agents. Presented herein is a subset of data from a larger study evaluating the potential effects of SNAC on the gestation, parturition, lactation, maternal behavior, and offspring development of rats. Pregnant Crl:CD BR VAF/Plus female rats (F(0); n = 25) received SNAC at 1000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For SNAC, Riley et al carried out a sub-chronic oral toxicity test of SNAC in rats and found a no observed adverse effect (NOAEL) level of 1 g/kg/day in rats for up to 13 weeks; it was only a massive dose of 2 g/kg/day that eventually caused significant mortality [78]. It was also examined for gestational toxicity in pregnant rats at oral doses up to 1 g/kg/day where slight weight loss was seen; there was no effect on growth of pups, but some evidence of a small increase in the still-birth rate was noted [79]. Some GI effects including emesis and diarrhea were observed in studies involving monkeys at a dose of ≥1.8 g/kg/day [80].…”
Section: Safety Of Snac and C10 In Preclinical And Clinical Studiesmentioning
confidence: 99%
“…For SNAC, Riley et al carried out a sub-chronic oral toxicity test of SNAC in rats and found a no observed adverse effect (NOAEL) level of 1 g/kg/day in rats for up to 13 weeks; it was only a massive dose of 2 g/kg/day that eventually caused significant mortality [78]. It was also examined for gestational toxicity in pregnant rats at oral doses up to 1 g/kg/day where slight weight loss was seen; there was no effect on growth of pups, but some evidence of a small increase in the still-birth rate was noted [79]. Some GI effects including emesis and diarrhea were observed in studies involving monkeys at a dose of ≥1.8 g/kg/day [80].…”
Section: Safety Of Snac and C10 In Preclinical And Clinical Studiesmentioning
confidence: 99%
“…In the peri-and post-natal developmental toxicity study, oral administration of 1 g/kg/day from implantation to lactation of rats was conducted to evaluate the exposure and toxicity of SNAC in the uterus and breast milk of the offspring. There was no effect on the growth and development of surviving offspring exposed to SNAC, albeit that an increase in the number of stillbirths during pregnancy was observed [146]. Unlike MCFA, given that it does not exist in nature, SNAC may have more safety considerations.…”
Section: Tirf Microscopy (Frap Analysis)mentioning
confidence: 88%
“…47 Recently, SNAC has achieved a ''generally regarded as safe'' (GRAS) status concurrently with published data on its toxicity. 48,49 The second clinically tested approach to increase heparin oral bioavailability also relies on coadministration with drug delivery agents, namely permeation enhancers. LMWH has been successfully combined with medium chain fatty acids in gastro-resistant tablets and yielded 8% oral bioavailability of LMWH in phase 1 clinical trial.…”
Section: Clinical Studiesmentioning
confidence: 99%